Character Education in the Qur'an Surah Al-Isra' Verse 23: Study of the Value of Speaking Softly to Parents and Its Relevance in Modern Life - Syahdan Syahdan; Fuji Rahmadi P (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Character education is very important for every child who is born, because children will be the successors of the older generation in building the future, both in the family environment and in society. This research aims to understand what kind of obedience a child should have and how to speak gently towards parents, even those who are older than him. Methodology: This research method uses a qualitative method of literature study, which collects information from scientific papers and literature reviews, while the primary data are the Al-Qur'an and the translation of the Indonesian Ministry of Religion and the Tafsir Jalalain and the Tafsir Al-Mishbah, then the secondary data are in the form of books, journals, proceedings and scientific works related to character education. Main Findings: The results of this study explain that character education, especially speaking softly to parents, is very important for children in the modern era. The Qur'an, Surah Al-Isra verse 23 provides educational values ​​that are relevant to this day, namely direct commands from Allah SWT that must be obeyed, the prohibition of saying harsh words such as 'uff' to parents, and the recommendation to speak softly and politely to both parents. Novelty/Originality of this study: This research has novelty in its approach which integrates the values ​​of the Qur'an, especially Surah Al-Isra' verse 23, into the context of modern life in speaking softly to parents in forming the character of children who have noble morals amidst technological advances and socio-cultural changes.